Deteksi Dini Status Kesehatan Remaja Putri Sebagai Upaya Mempersiapkan Generasi Bebas Stunting di MAN Kota Mojokerto, Jawa Timur - Purwantari, Kusuma (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
Stunting remains a major public health problem that requires early prevention, particularly among adolescent girls as future mothers. This community service activity aimed to improve health knowledge and assess the nutritional status of adolescent girls as part of stunting prevention efforts. The activity involved 109 students and consisted of health education accompanied by nutritional status assessment using Body Mass Index (BMI) and Mid-Upper Arm Circumference (MUAC). Knowledge was evaluated through pre-test and post-test assessments. The results showed a significant improvement in knowledge, with the proportion of good knowledge increasing from 32.1% to 55.0% after the intervention. However, nutritional assessment revealed a high prevalence of low MUAC (60.4%), as well as underweight (22.6%) and overweight (9.4%) based on BMI. These findings indicate that while health education improves knowledge, continuous nutrition education, regular monitoring, and targeted nutritional interventions are needed to prevent intergenerational stunting. Keywords: stunting, health education, adolescent girl, nutritional status